A history of slavery and emancipation in Iran, 1800-1929 - Mirzai, Behnaz A. (University of Texas Press, 2017)
Slavery in the Middle East is a growing field of study, but the history of slavery in a key country, Iran, has never before been written. This history extends to Africa in the west and India in the east, to Russia and Turkmenistan in the north, and to the Arab states in the south. As the slave trade between Iran and these regions shifted over time, it transformed the nation and helped forge its unique culture and identity. Thus, a history of Iranian slavery is crucial to understanding the character of the modern nation. Drawing on extensive archival research in Iran, Tanzania, England, and France, as well as fieldwork and interviews in Iran, Behnaz A. Mirzai offers the first history of slavery in modern Iran from the early nineteenth century to emancipation in the mid-twentieth century. She investigates how foreign military incursion, frontier insecurity, political instability, and economic crisis altered the patterns of enslavement, as well as the ethnicity of the slaves themselves. Mirzai's interdisciplinary analysis illuminates the complex issues surrounding the history of the slave trade and the process of emancipation in Iran, while also giving voice to social groups that have never been studied-enslaved Africans and Iranians. Her research builds a clear case that the trade in slaves was inexorably linked to the authority of the state. During periods of greater decentralization, slave trading increased, while periods of greater governmental autonomy saw more freedom and peace.